Pandangan Islam tentang Globalisasi: Analisis Tafsir Maudhu’i - Ghina Salsabila; Hanifatul Akmila; Indi Ariqah Putri Dadi; Luthfi Muhammad Hamdani; Asep Abdul Muhyi (UIN Sunan Gunung Djati Bandung, 2023)
This paper discusses Islam dan globalization. This study uses a descriptive methodology and maudhu’i interpretation. A qualitative research methodology that relies on secondary data sources, namely works of literature related to research topics taken from books, journal articles, and other sources. The historical facts of globalization have had a major impact on every individual in living life. A wise response must be made in the face globalization. Islam is a religion with a universal and global order has contributed to solving the issue of globalization. That universality of Islam proves that Islam has a huge impact on how the world will be. Islamic universalism can be observed in various ways such as cosmopolitan cultural teachings, scientific progress, holistic social structures, and plenary ideals. Islam has the ability to overcome problems in the fields of technology, economics, education, and other problems. Islamic teachings instruct Muslims to avoid falling into imitation or rejection in the negative context of globalization. In line with adherence to Islamic values, as well as tolerance and understanding of reality, Islam teaches how to be objective.